Dergi Hakem Kurulu - (:unkn) unknown (My University, 2017)
Prof. Dr. Turgut KARABEY Prof. Dr. Yusuf ÇETİN Prof. Dr. Zahide İMER Doç. Dr. Ahmet Şinasi İŞLER Doç. Dr. Ali Yalçın TAVUKÇU Doç. Dr. Cengiz ŞENGÜL Doç. Dr. Gökalp Nuri SELÇUK Doç. Dr. Hagigat MUHARREMOVA Doç. Dr. Korkmaz MERAL Doç. Dr. Mete DEMİRBAŞ Doç. Dr. Mustafa BEYAZIT Doç. Dr. Mümtaz DEMİRKALP Doç. Dr. Nesrin FEYZİOĞLU Doç. Dr. Nurettin KOÇHAN Doç. Dr. Selma ELYILDIRIM Doç. Dr. Yakup GÖKDAŞ Doç. Dr. Yunus BERKLİ Yrd. Doç. Dr. Cemal SEVİNDİ Yrd. Doç. Dr. Hasan AKDAĞ Yrd. Doç. Dr. Muhammet Lütfü KINDIĞILI (Atatürk Üniversitesi) Yrd. Doç. Dr. Serhat YENER Yrd. Doç. Dr. Yusuf BİLEN Yrd. Doç. Dr. Zerrin KÖŞKLÜ
Keywords: Tarih